Viability, productivity, and anatomical response of groundnuts (Arachis hypogaea L.) to biofertilizer-sludge biogas applications - Nur Hidayah Pangestuti; Dwi Umi Siswanti (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Groundnuts (Arachis hypogaea L.) is one of the essential food commodities in Indonesia. The use of biofertilizer has been applied to various types of crops. Meanwhile, the effect of using biofertilizer-sludge biogas on groundnuts is yet unknown. This study aims to analyze the seed viability and vigour, yield productivity, the anatomical response of groundnuts, and optimum concentration that could increase the values of each parameter. Treatments given include applying biofertilizer-sludge with 15 levels of treatment concentration compared to groundnuts without biofertilizer-sludge application as a control. The land was divided into 16 beds for each treatment consisting of control, biofertilizer from 10, 15, 30 L/ha, sludge from 12, 24, to 36 ml, and variations dosage of biofertilizer and sludge combined. The parameters observed for viability and vigour include the percentage of seed germination (GP), seed vigor index (SVI) for yield, the value of harvest index (HI), dry weight of the harvest, and root-shoot ratio (R/S). Anatomical responses were observed with stem diameter, stem’s metaxylem diameter, root diameter, root’s metaxylem diameter, and seed diameter. The biofertilizer-sludge results significantly affected HI, R/S values, stem diameter, root’s metaxylem diameter, and seed diameter. This research concluded that the application of biofertilizer-sludge did not significantly affect the seed viability and vigour and the dry weight of the harvest. The application of biofertilizer-sludge in various doses of concentration resulted in a decrease in the stem metaxylem diameter and root diameter compared to the control. A total of 10 L/ha biofertilizer + 24 ml sludge was an optimum concentration to increasing HI and R/S values. For the increasing stem, root metaxylem, and seed diameter, biofertilizer 30 L/ha + sludge 12 ml, sludge 24 ml, and biofertilizer 15 L/ha + sludge 12 ml were the optimum concentrations, respectively.